Analisis Modal Sosial dalam Kepemimpinan Kepala Desa Sewangi: Studi Kasus Berdasarkan Teori Modal Sosial Putnam - Khairussalam, Khairussalam; Zulaikha, Siti; Isnaeni Nur, Ririn; Maimunah, Siti (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research aims to analyze the role of social capital in the context of village head leadership using the social capital theory framework proposed by Robert D. Putnam. This social capital includes three main elements: trust, social norms, and social networks. This study is a case study involving several villages in order to understand how social capital influences the leadership quality of village heads. Data was collected through interviews with village heads, community members and local stakeholders. Data analysis was carried out by identifying and evaluating the level of trust in society, the social norms that guide the village head's behavior, and the social networks built by the village head in carrying out his duties. The research results show that social capital has a significant impact on the leadership quality of village heads. Village heads who can build and maintain a high level of trust in their community tend to be more effective in carrying out their duties. In addition, social norms that value integrity and transparency in leadership have a positive influence on leadership quality. Strong social networks also help village heads access the resources and support needed to overcome challenges This study provides in-depth insight into how social capital plays a role in the context of village head leadership and has important implications for the development of more effective leadership policies and practices at the village level. Future research could delve deeper into specific aspects of social capital that have a significant impact in the context of village leadership.